Chronic mild stress induced anxiety-like behaviors can Be attenuated by inhibition of NOX2-derived oxidative stress. (July 2019) - Lv, Hang; Zhu, Chuan'an; Wu, Ruolin; Ni, Hui; Lian, Jiating; Xu, Yunlong; Xia, Yucen; Shi, Guoqi; Li, Zhixing; Caldwell, Ruth B.; Caldwell, Robert William; Yao, Lin; et al.
Abstract: Chronic stress-induced anxiety disorder is a highly-prevalent, modern social disease in which oxidative stress plays an important role. It is necessary to determine the underlying mechanisms governing this disorder to establish an effective treatment target for anxiety disorders. In this study, we examined the behavioral changes in mice subjected to chronic mild stress (CMS). We found that CMS exposure leads to anxiety-like phenotypes and increased levels of oxidative stress in the ventral hippocampus of mice. Furthermore, CMS increased the excitatory synaptic transmission of pyramidal cells in the ventral CA1 (vCA1). Administration of 4-hydroxy-3-methoxy-acetophenone (apocynin), an inhibitor of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidases, clearly ameliorated the changes induced by CMS exposure. In addition, our results of behavioral tests and analyses of reactive oxygen species (ROS) using NOX2-deficient mice indicate that CMS-induced enhanced oxidative stress level is primarily caused by the increased expression of NOX2. NOX2-derived oxidative stress can serve as a target for anxiety therapy led by chronic stress.